Manufacturing method of artificial rock core for simulating CO2-water-rock reaction under control of diffusion effect in formation fracture

By using high-purity olive powder to make artificial rock hearts and simulate the complex structure of stratigraphy cracks, it is difficult to accurately simulate the problem of stratigraphic cracks, and improves the authenticity and reliability of the CO2-water-rock reaction experiment.

CN119334722AInactive Publication Date: 2025-01-21SOUTHWEST PETROLEUM UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411605175.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-01-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing core production methods are difficult to accurately simulate the complex geometric characteristics of formation fractures, which affects the authenticity and reliability of experimental results of CO2-water-rock reactions.

Method used

Use high -purity olive powder to make artificial rock hearts. By regulating compact pressure and particle size composition, the target pore degree is obtained, cutting and milling to form complex geometric cracks. "Blind cracks".

Benefits of technology

The precise simulation of stratigraphy cracks is achieved, the experimental effect of the CO2-water-rock reaction is improved, and the response products are facilitated to observe and detect the reaction product, and the accuracy and authenticity of the experimental results is ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119334722A_ABST
    Figure CN119334722A_ABST
Patent Text Reader

Abstract

The invention provides a manufacturing method of an artificial rock core for simulating a CO2-water-rock reaction under the control of a diffusion effect in a formation fracture. The method relates to the technical field of geochemical water-rock reaction, and comprises the following steps: obtaining target rock powder and target stratum data, including porosity and fracture parameters; obtaining compaction pressure, particle size composition and cementing agent proportion data of the artificial cores with different porosities; mixing the rock powder with different granularities and the cementing agent in proportion, filling, compacting, baking and forming; the method comprises the following steps: cutting a molded rock core, milling cracks, coating and bonding the side surfaces and the bottom surface of the rock core with epoxy resin glue, only exposing the top surface with the cracks, and accurately simulating real stratum cracks through cutting and milling; epoxy resin can still keep the performance unchanged under the conditions of high temperature, high pressure and corrosion, blind end cracks in a simulated stratum are coated and sealed on the bottom face and the side face of the rock core, the blind end cracks are easy to remove after reaction, reaction products and the internal conditions of the cracks are convenient to observe, and the method has excellent application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of geochemical water-rock reaction processes, and in particular to a method for simulating the diffusion control of CO in formation fractures. 2 -Method for making artificial rock core by water-rock reaction. Background Art

[0002] As global climate change intensifies, the greenhouse effect problem needs to be solved urgently. Carbon capture and storage (CCS) technology is a technology that can reduce atmospheric CO 2 CCS technology refers to the separation of carbon dioxide produced by industry and related energy industries through carbon capture technology, and then transporting and sealing it to the seabed or underground and other places isolated from the atmosphere through carbon storage. This technology is considered to be one of the most feasible ways to reduce greenhouse gas emissions and slow global warming on a large scale in the future. 2 There are mainly geological storage, marine storage and oil and gas field storage. Among geological storage, mineralization storage is a method of storing CO 2 A technology that injects CO into underground geological formations and converts it into stable carbonate minerals through chemical reactions with minerals. 2 Dissolving in water lowers the pH and accelerates the dissolution of silicate minerals. The dissolution of minerals releases divalent cations, which increases the pH and promotes the formation of carbonate minerals. This process not only effectively reduces CO 2 It also provides a long-term and stable storage solution.

[0003] As a mafic rock rich in divalent cations, basalt can efficiently convert injected CO 2 Converted into carbonate rock to achieve CO 2 Safe and effective permanent storage of CO 2 Mineral storage shows great potential. At present, field tests have proved that basalt CO 2 The huge potential of mineralized storage includes the Carbfix project in Iceland, the Wallula project in the United States, and the Nagaoka project in Japan. Among them, the Icelandic CarbFix project found through isotope tracing that CO injected into the basalt formation within two years 2 The mineralization rate is over 95%. Olivine (Mg, Fe) 2 SiO 4 ) is a mineral with the fastest dissolution rate and the highest carbonate formation potential among the minerals found in basalt, and it has great research value.

[0004] CO 2The cost of field application of mineralization storage technology is high, so artificial cores need to be made for indoor testing. The existing core making method usually includes rock powder processing, compaction and molding steps to simulate CO 2 Diffusion and reaction in underground rock formations. Fractures in actual formations react with CO 2 The impact of the storage process cannot be ignored. It not only provides CO 2 The diffusion channel will also be the chemical reaction area. The reaction rate and product distribution in the fracture are significantly different from those in the non-fracture area. However, these traditional methods are not very effective in simulating actual formation fractures and their effects on CO 2 There are obvious deficiencies in the impact of the reaction. Because it is difficult for traditional cores to accurately simulate the complex geometric characteristics of fractures, the authenticity and reliability of the experimental results are greatly affected. Therefore, accurate simulation of fractures is very important for predicting CO 2 The stability of long-term burial and its environmental impact are of great significance. In addition, under high temperature and high pressure conditions, the stability and sealing of ordinary adhesive materials may not meet the experimental requirements, which will also affect the experimental results.

[0005] In existing research, indoor experiments basically use natural basalt cores, but basalt has complex composition and is difficult to detect in indoor CO 2 -The carbon fixation effect in the water-rock diffusion reaction study is not good. The cores produced by the existing technology are generally complete cores, and it is not easy to observe and detect the reaction effect in the core cracks after the reaction, and CO 2 -The water-rock diffusion reaction system requires the formation of a "blind-end crack" in the core (a crack in a porous medium that is connected to other cracks at one end and closed at the other end) to meet the prerequisite for diffusion reaction. Olivine is the mineral with the fastest dissolution rate and the greatest carbonate formation potential in basalt. Therefore, in order to better study the CO 2 Mineral sealing mechanism, the present invention uses high-purity olivine powder to make cores. By adjusting parameters such as compaction pressure and rock powder particle size, an artificial core with a target porosity is obtained. After the core is made, it is cut and milled to accurately simulate real formation cracks, and then the bottom and sides of the core are coated and sealed with a special epoxy resin AB glue, leaving only the crack opening on the top surface, solving the problems of poor reaction effect of natural basalt cores, difficulty in observing and detecting the internal reaction effect of the core after the reaction, and difficulty in forming "blind-end cracks" in artificial cores. The invention has the advantages of accurately simulating formation cracks, good reaction effect, and easy detection and observation of experimental effects after the reaction. Summary of the invention

[0006] In view of this, in order to solve the above technical problems, the present invention aims to provide a method for simulating the diffusion control of CO in formation fractures. 2- A method for making an artificial core by water-rock reaction; the steps include: obtaining target rock powder and target formation data, including porosity and crack parameters; obtaining compaction pressure, particle size composition and binder ratio data of artificial cores with different porosities; mixing rock powder and binder of different particle sizes in proportion, filling and compacting, and baking to form; cutting and milling the formed core to form the cracks, and then coating and bonding the side and bottom surfaces of the core with special epoxy resin glue, leaving only the top surface with cracks exposed, and accurately simulating real formation cracks through cutting and milling; the special epoxy resin can still maintain its performance unchanged under high temperature, high pressure and corrosion conditions, and the bottom and sides of the core are coated and sealed to simulate the "blind end cracks" in the formation, which are easy to remove after the reaction to facilitate observation of the reaction products and the internal conditions of the "cracks", and have excellent application and promotion prospects.

[0007] In order to achieve the above technical objectives, the technical solutions adopted are as follows:

[0008] A method to simulate the diffusion-controlled CO 2 -The method for making an artificial rock core by water-rock reaction comprises the following steps:

[0009] Step S1: obtaining rock powder and target formation data of the target formation, the target formation data including porosity and fracture parameters; and analyzing the main factors affecting the porosity of other artificial cores or artificial cores of the target formation;

[0010] Step S2: according to the main influencing factors in step S1, obtaining the particle size composition, compaction pressure and added binder ratio data of the target formation rock powder;

[0011] Step S3: Put the target stratum rock powder in a beaker, add a solvent, and stir mechanically. After stirring, let it stand, pour out the upper suspension to remove impurities in the rock powder, repeat the above cleaning steps until the upper liquid is free of impurities, filter it, and place it in an oven for drying to obtain the target stratum rock powder;

[0012] Step S4: drying the target formation rock powder cleaned in step S3, and sieving rock powders of different particle sizes through a vibrating screen for later use;

[0013] Step S5: according to the porosity of the artificial core of the target formation, the particle size composition of the rock powder, the compaction pressure and the ratio of the added binder, the rock powders of different particle size ranges are uniformly mixed with the binder in proportion;

[0014] Step S6: pour the evenly mixed powder into the core mold in multiple times, and each time the mixed powder is poured in, it needs to be manually pressed and filled with an iron rod with the same inner diameter as the core mold;

[0015] Step S7: After the filling is completed, the iron rod is inserted into the mold and placed under the hydraulic press for compaction for a period of time until the iron rod does not move relative to the mold;

[0016] Step S8: baking the compacted artificial core together with the mold for a period of time, cooling to room temperature, and taking out the artificial core;

[0017] Step S9: measuring the porosity of the manufactured artificial core using a porosity measuring instrument, and analyzing the error between the measured porosity and the target porosity;

[0018] Step S10: Cut the manufactured artificial core into short cores, and then cut the small core into two half cylinders. According to the crack parameters in step S1, use a precision CNC milling machine to mill complex geometric groove cracks on a cut surface, and confirm the groove depth under an optical microscope;

[0019] Step S11: the cut core is cleaned to remove the residual chemicals from the cutting process, then ultrasonically treated in deionized water to remove any fine particles generated during the cutting process, and then placed in an oven to dry to constant weight;

[0020] Step S12: merge the two dried semi-cylinders together, then apply epoxy resin glue on the side and bottom surfaces, leaving only the top surface with the crack entrance exposed, and bake the core in a constant temperature oven to accelerate solidification;

[0021] Step S13: After the epoxy resin glue is completely solidified, the core is taken out, and the CO2 under the control of diffusion in the simulated formation fracture is 2 -The artificial core of water-rock reaction is completed.

[0022] Furthermore, the target formation rock powder in step S1 is olivine powder with a purity of 90-99%; the main factors are the particle size composition of the rock powder, the compaction pressure and the proportion of the added binder.

[0023] Furthermore, in step S3, the solvent is anhydrous ethanol, the mixture is mechanically stirred for 5-10 minutes at a stirring speed of 100-500 rpm, and then allowed to stand for 30-60 minutes.

[0024] Furthermore, in step S4, the target formation rock powder is placed in a constant temperature oven at 65-70°C and dried to constant weight and then taken out; the different particle size ranges of the screened rock powder in step S4 are: 70-100 mesh, 100-120 mesh, 120-150 mesh, 150-300 mesh, and ≥300 mesh.

[0025] Furthermore, the ratio of the binder in step S5 is 5-10%; the total mass of the rock powders of different particle size ranges and the binder in step S5 is 50-70g.

[0026] Furthermore, in step S6, the uniformly mixed powder is poured into a core mold with a diameter of 2.54 cm in 2-5 times.

[0027] Furthermore, the core compaction pressure in step S7 is 1-2 MPa, and the compaction time is 5-10 minutes; the baking temperatures in step S8 are: 98-100° C. for 6-7 hours, 140-150° C. for 3-4 hours, and 190-200° C. for 40-50 minutes.

[0028] Furthermore, the size of the short core in step S10 is φ2.54-3.8×2-4 cm; the depth of the complex geometric groove crack is micron level.

[0029] Furthermore, in step S11, the cut core is cleaned with acetone; and ultrasonically treated in deionized water for more than 2 times, each time for 5-10 minutes.

[0030] Furthermore, the epoxy resin glue in step S12 is epoxy resin AB glue that is resistant to high temperature, high pressure, acid and alkali corrosion.

[0031] Beneficial effects:

[0032] The beneficial effects of the present invention are embodied in:

[0033] (1) The artificial core produced by the present invention uses high-purity olivine as the main material. Olivine has the fastest dissolution rate and the highest carbonate formation potential among the constituent minerals of basalt, thereby achieving better experimental results and facilitating in-depth research on CO in basalt. 2 In addition, the porosity of different basalt formations can be simulated by adjusting the compaction pressure of the core and the particle size of the olivine powder.

[0034] (2) After the artificial core produced by the present invention is cut, micro cracks with complex geometric shapes are milled in the middle to enhance the core reaction effect. After the reaction is completed, the epoxy resin glue can be removed to facilitate the observation of the internal reaction effect without destroying the integrity of the reaction product. At the same time, the special epoxy resin glue has excellent high temperature, high pressure and acid and alkali corrosion resistance, CO 2 After dissolving in the solution, it will not react with it, thus ensuring the accuracy and authenticity of the experimental results. 2 A prerequisite for the diffusion reaction is that the core must have a "blind-end crack", and the epoxy resin glue completely seals the sides and bottom of the core, leaving only the top, thus forming a "blind-end crack" to ensure the smooth progress of the experiment. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0036] Figure 1 is a preparation flow chart of an embodiment of the present invention;

[0037] Figure 2 This is a schematic diagram of the structure of an artificial core according to an embodiment of the present invention;

[0038] Among them: 1 is a semi-cylindrical core with milled fractures, 2 is a semi-cylindrical core without milled fractures, and 3 is epoxy resin glue;

[0039] Figure 3 This is a real picture of the artificial core after applying epoxy resin glue in the embodiment of the present invention;

[0040] Figure 4 This is a real picture of the top surface of the artificial core with cracks after epoxy resin glue is applied in the embodiment of the present invention;

[0041] Figure 5 This is a scanning electron microscope image of the milled area inside the core after the olivine core reaction;

[0042] Figure 6 Scanning electron microscope image of the milled area inside the basalt core after reaction. DETAILED DESCRIPTION

[0043] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0044] Example 1

[0045] like Figure 1 A simulation of CO diffusion in formation fractures 2 -The method for making an artificial rock core by water-rock reaction comprises the following steps:

[0046] (1) Obtain the target olivine powder with a purity of 90%. Its main components and mass fractions can be seen in Table 1. According to the analysis of basalt formation data from various places, the porosity of basalt formations is usually 1-20%. In order to better restore the real formation environment, the particle size composition, compaction pressure and proportion of added binder of the artificial core are analyzed and controlled to make the porosity of the produced core within the range of 1-20%.

[0047] Table 1 Main components and mass fractions of olivine powder

[0048] Composition <![CDATA[Al 2 THE 3 ]]> <![CDATA[SiO 2 ]]> <![CDATA[Fe 2 THE 3 ]]> CaO MgO Mass fraction, % 1.25 41.00 9.03 1.18 45.68

[0049] (2) By analyzing the influence of factors such as particle size composition, compaction pressure and proportion of added binder on the porosity of artificial cores of the same type, the rock powder particle size composition, compaction pressure, and proportion of binder of olivine cores with different porosities were confirmed, as shown in Table 2.

[0050] Table 2 Particle size composition, compaction pressure and binder ratio of olivine cores with different porosities

[0051]

[0052] (3) Place 500 g of newly obtained olivine powder in a beaker, add anhydrous ethanol so that the surface is 3 cm higher than the rock powder, and stir mechanically for 5-10 minutes at a stirring speed of 100-500 rpm. After stirring, let it stand for 30 minutes, and then slowly pour out the upper suspension to remove impurities generated by the rock powder during mining and crushing. Repeat the above cleaning steps until the upper liquid is free of impurities, then slowly pour out the upper liquid and place it in a constant temperature oven at 65°C for drying.

[0053] (4) The olivine powder washed in step (3) is dried in a constant temperature oven to constant weight and then taken out, and 70-100 mesh, 100-120 mesh, 120-150 mesh, 150-300 mesh, and ≥300 mesh sieves are used to sieve out olivine powder with particle sizes of 70-100 mesh, 100-120 mesh, 120-150 mesh, 150-300 mesh, and ≥300 mesh for later use.

[0054] (5) Through the analysis of data from other artificial cores of the same type, the binder ratio in this example is 10%. The total weight of rock powder and binder for olivine cores with target porosities of 20%, 15%, and 10% are 70 g, 65 g, and 60 g, respectively. The mass ratios of olivine powders with different particle sizes are shown in Table 2.

[0055] (6) Take olivine powder of corresponding particle size and binder according to the proportion in Table 2 and mix them evenly. Then pour them into a core mold with a diameter of 2.54 cm three times. Each time the mixed powder is poured, it needs to be manually compacted with an iron rod with the same diameter as the core mold. Repeat the above steps to make three cores for each target porosity.

[0056] (7) After filling, insert the iron rod into the mold and place it under the hydraulic press. Set the compaction pressure. The compaction pressures of the olivine core with target porosity of 0%, 15%, and 10% are 1.00 MPa, 1.25 MPa, and 1.50 MPa, respectively. Use the hydraulic press to squeeze the iron rod downward. After the pressure stabilizes, continue compacting for 5-10 minutes until the iron rod no longer has relative displacement with the mold.

[0057] (8) The compacted artificial rock and the mold are placed in a constant temperature oven and baked in three stages: 98°C for 6 h, 140°C for 3 h, and 200°C for 40 min. After baking, wait for the oven to cool to room temperature and take out the core.

[0058] (9) The porosity of the prepared core was measured using a pore-permeability tester. The measured porosity is shown in Table 3.

[0059] Table 3 Measured porosity

[0060]

[0061]

[0062] It can be seen from Table 3 that the measured average porosities of olivine cores with target porosities of 20%, 15%, and 10% are 19.67%, 15.63%, and 9.53%, respectively, and the errors are all within 5%.

[0063] (10) Figure 2 As shown, the prepared olivine core is cut into short cores with a size of φ2.54×2.0 cm, and then the short core is cut in half into two semi-cylinders. A geometric micro-crack (a straight groove is used as an example in this embodiment) is milled on the cross-section of one of the semi-cylinders using a precision CNC milling machine. The straight groove has a length of 2.0 cm, a width of 1.1 cm, and a depth of 100 μm. The unmilled portion and the cross-section of the other semi-cylinder are polished with sandpaper, and the groove depth is determined by comparing the z values ​​of the points on the groove surface and the points on the polished surface under an optical microscope.

[0064] (11) After cutting, the half cylinders were washed with acetone to remove residual chemicals from the cutting process, and then sonicated in deionized water twice for 5 min each to remove acetone and any fine particles generated during the cutting process, and then placed in an oven to dry to constant weight.

[0065] (12) Figure 3-Figure 4 As shown, two dried semi-cylinders are connected together, a small amount of 502 glue is applied to the side joint of the core to fix the core, and then a special high temperature, high pressure, acid and alkali corrosion resistant epoxy resin AB glue is applied to the side and bottom surfaces, leaving only the top surface with the crack entrance exposed, and then the core is placed in a constant temperature oven, the temperature is set to 70°C, and baked for 2 hours to accelerate solidification.

[0066] (13) After the epoxy resin glue is completely solidified, the core is taken out and the artificial core is completed.

[0067] The basalt core XWY201 with a measured porosity of 19.1% produced in the same steps as above (the only difference from the present invention is that there is no milling of geometric microcracks, and the produced short core also needs to be broken into two semi-cylinders, which is consistent with the present invention) and the GLS201 core were used for comparative experiments. The two cores were placed in two saturated CO 2 The aqueous solution was then placed in a beaker in a high-temperature and high-pressure reactor, with the temperature set at 100°C and the pressure set at 12 MPa for 14 days. After the reaction was completed, the core was taken out and the epoxy resin glue was removed. The formation of carbonate minerals in the milling area inside the core was observed by scanning electron microscopy. The scanning electron microscope image of the GLS201 core is shown in the figure. Figure 5 As shown in the figure, a large number of cubic magnesium carbonate mineral precipitation groups can be found. The electron microscope image of the XWY201 core is shown in Figure 6 As shown, no obvious carbonate mineral formation was found in the figure.

[0068] In summary, the artificial core made by the present invention uses high-purity olivine as the main material. Olivine has the fastest dissolution rate and the highest carbonate formation potential among the constituent minerals of basalt, so that better experimental results can be achieved, which is convenient for in-depth research on CO in basalt. 2 The mechanism of mineralization sealing. In addition, the porosity of different basalt formations can be simulated by adjusting the compaction pressure of the core and the particle size composition of the olivine powder. After cutting, the artificial core made by the present invention is milled with straight grooves in the middle to form micro cracks to enhance the core reaction effect. After the reaction is completed, the epoxy resin glue can be removed to facilitate the observation of the internal reaction effect and ensure the integrity of the reaction product. At the same time, the special epoxy resin glue is evenly applied to the side and bottom of the core. Because it has excellent resistance to high temperature, high pressure and acid and alkali corrosion, CO 2 After dissolving in the solution, it will not react with it, thus ensuring the accuracy and authenticity of the experimental results. 2 A prerequisite for diffusion reaction is that the core must have a "blind-end crack", and the epoxy resin glue completely seals the sides and bottom of the core, leaving only the top, thus forming a "blind-end crack". It is easy to remove after the reaction to facilitate observation of the reaction products and the internal conditions of the "crack", which can ensure the smooth progress of the experiment and has excellent prospects for application and promotion.

[0069] The above description is not intended to impose any form of limitation on the present invention. Although the present invention has been disclosed through the above embodiments, it is not intended to limit the present invention. Any technician familiar with the profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A method for making an artificial core that simulates the CO2-water-rock reaction controlled by diffusion in formation fractures, characterized in that: The method comprises the following steps: Step S1: obtaining rock powder and target formation data of the target formation, the target formation data including porosity and fracture parameters; and analyzing the main factors affecting the porosity of other artificial cores or artificial cores of the target formation; Step S2: according to the main influencing factors in step S1, obtaining the particle size composition, compaction pressure and added binder ratio data of the target formation rock powder; Step S3: Put the target stratum rock powder in a beaker, add a solvent, and stir mechanically. After stirring, let it stand, pour out the upper suspension to remove impurities in the rock powder, repeat the above cleaning steps until the upper liquid is free of impurities, filter it, and place it in an oven for drying to obtain the target stratum rock powder; Step S4: drying the target formation rock powder cleaned in step S3, and sieving rock powders of different particle sizes through a vibrating screen for later use; Step S5: according to the porosity of the artificial core of the target formation, the particle size composition of the rock powder, the compaction pressure and the ratio of the added binder, the rock powders of different particle size ranges are uniformly mixed with the binder in proportion; Step S6: pouring the evenly mixed powder into the core mold in multiple times, and manually pressing and filling with an iron rod having the same inner diameter as the core mold each time the mixed powder is poured; Step S7: After the filling is completed, the iron rod is inserted into the mold and placed under the hydraulic press for compaction for a period of time until the iron rod does not move relative to the mold; Step S8: baking the compacted artificial core together with the mold for a period of time, cooling to room temperature, and taking out the artificial core; Step S9: measuring the porosity of the manufactured artificial core using a porosity measuring instrument, and analyzing the error between the measured porosity and the target porosity; Step S10: Cut the manufactured artificial core into short cores, and then cut the small core into two half cylinders. According to the crack parameters in step S1, use a precision CNC milling machine to mill complex geometric groove cracks on a cut surface, and confirm the groove depth under an optical microscope; Step S11: the cut core is cleaned to remove the residual chemicals from the cutting process, then ultrasonically treated in deionized water to remove any fine particles generated during the cutting process, and then placed in an oven to dry to constant weight; Step S12: merge the two dried semi-cylinders together, then apply epoxy resin glue on the side and bottom surfaces, leaving only the top surface with the crack entrance exposed, and bake the core in a constant temperature oven to accelerate solidification; Step S13: After the epoxy resin glue is completely solidified, the core is taken out, and the artificial core simulating the CO2-water-rock reaction controlled by the diffusion effect in the formation fracture is completed.

2. The method for making an artificial core for simulating the CO2-water-rock reaction controlled by diffusion in formation fractures according to claim 1, characterized in that: The target formation rock powder in step S1 is olivine powder with a purity of 90-99%; the main factors are the particle size composition of the rock powder, the compaction pressure and the proportion of the added binder.

3. The method for making an artificial core for simulating the CO2-water-rock reaction controlled by diffusion in a formation fracture according to claim 1, characterized in that: In step S3, the solvent is anhydrous ethanol, and the mixture is mechanically stirred for 5-10 minutes at a stirring speed of 100-500 rpm. After the stirring, the mixture is allowed to stand for 30-60 minutes.

4. The method for making an artificial core for simulating the CO2-water-rock reaction controlled by diffusion in formation fractures according to claim 1, characterized in that: In step S4, the target formation rock powder is placed in a constant temperature oven at 65-70°C and dried to constant weight and then taken out; the different particle size ranges of the screened rock powder in step S4 are: 70-100 mesh, 100-120 mesh, 120-150 mesh, 150-300 mesh, and ≥300 mesh.

5. The method for making an artificial core for simulating the CO2-water-rock reaction controlled by diffusion in formation fractures according to claim 1, characterized in that: The ratio of the binder in step S5 is 5-10%; the total mass of the rock powder of different particle size ranges and the binder in step S5 is 50-70g.

6. The method for making an artificial core for simulating the CO2-water-rock reaction controlled by diffusion in formation fractures according to claim 1, characterized in that: In step S6, the uniformly mixed powder is poured into a core mold with a diameter of 2.54 cm in 2-5 times.

7. The method for making an artificial core for simulating the CO2-water-rock reaction controlled by diffusion in a formation fracture according to claim 1, characterized in that: The core compaction pressure in step S7 is 1-2 MPa, and the compaction time is 5-10 minutes; the baking temperature in step S8 is: 98-100° C. for 6-7 hours, 140-150° C. for 3-4 hours, and 190-200° C. for 40-50 minutes.

8. The method for making an artificial core for simulating the CO2-water-rock reaction controlled by diffusion in formation fractures according to claim 1, characterized in that: The size of the short core in step S10 is φ2.54-3.8×2-4 cm; the depth of the complex geometric groove crack is micron level.

9. The method for making an artificial core for simulating the CO2-water-rock reaction controlled by diffusion in formation fractures according to claim 1, characterized in that: In step S11, the cut core is cleaned with acetone and ultrasonically treated in deionized water for more than 2 times, each time for 5-10 minutes.

10. The method for making an artificial core for simulating the CO2-water-rock reaction controlled by diffusion in formation fractures according to claim 1, characterized in that: The epoxy resin glue in step S12 is epoxy resin AB glue that is resistant to high temperature, high pressure, acid and alkali corrosion.